Biomarkers as outcome predictors in subarachnoid hemorrhage – a systematic review. (March 2014) - Hong, Caron M.; Tosun, Cigdem; Kurland, David B.; Gerzanich, Volodymyr; Schreibman, David; Simard, J. Marc
Abstract Context: Subarachnoid hemorrhage (SAH) has a high fatality rate and many suffer from delayed neurological deficits. Biomarkers may aid in the identification of high-risk patients, guide treatment/management and improve outcome. Objective: The aim of this review was to summarize biomarkers of SAH associated with outcome. Methods: An electronic database query was completed, including an additional review of reference lists to include all potential human studies. Results: A total of 298 articles were identified; 112 were reviewed; 55 studies were included. Conclusion: This review details biomarkers of SAH that correlate with outcome. It provides the basis for research investigating their possible translation into the management of SAH patients.